PERLINDUNGAN HUKUM TERHADAP KORBAN KEKERASAN DALAM RUMAH TANGGA (KDRT): PERLINDUNGAN HUKUM TERHADAP KORBAN KEKERASAN DALAM RUMAH TANGGA (KDRT) - bambang ali kusumo; Supriyanta Supriyanta; Regia Cahaya (Adi Widya : Jurnal Pengabdian Masyarakat, 2023)
The purpose of this service is to find out how the legal protection for victims of domestic violence according to Law no. 23 of 2004 concerning the Elimination of Domestic Violence and what are the obstacles or obstacles that arise in the implementation of protection for victims of Domestic Violence (KDRT). The method in this community service is by means of lectures and discussions. Legal protection for victims of domestic violence is very much needed because all forms of violence, especially domestic violence are violations of human rights and crimes against human dignity and forms of discrimination. Victims of physical-psychological violence, sexual and neglect experience suffering and losses, so it is necessary to protect the rights of victims to obtain justice. The obstacle or obstacle that arises in the implementation of protection for victims of domestic violence is that domestic violence is often not reported to the police, because victims feel ashamed to open up household problems to other parties. family